2013
DOI: 10.1007/s10461-013-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Evaluation of Correlates of HIV Testing Practices Among Men Who Have Sex with Men (MSM) in Mongolia

Abstract: This study analyzed patterns and associations of HIV testing including sexual practices, HIV related knowledge, and human rights contexts among MSM in Mongolia. 313 participants were accrued using respondent-driven sampling and administered a structured questionnaire. Descriptive statistics are presented with crude and adjusted-point estimates with confidence intervals (95 % CI); and logistic regression models were used to identify factors associated with HIV testing in the last 12 months. RDS-adjustment demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In addition, MSM who reported using a condom with last casual male partner were more likely to have disclosed information to a healthcare provider. This may indicate that MSM who disclose are receiving appropriate care including counselling on condom use, similar to studies in other contexts which have found disclosure to be associated with HIV protective behaviours [ 59 , 60 ]. Conversely, it may indicate that individuals at the greatest risk for acquiring anal STIs are not comfortable disclosing and therefore are not receiving appropriate care.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, MSM who reported using a condom with last casual male partner were more likely to have disclosed information to a healthcare provider. This may indicate that MSM who disclose are receiving appropriate care including counselling on condom use, similar to studies in other contexts which have found disclosure to be associated with HIV protective behaviours [ 59 , 60 ]. Conversely, it may indicate that individuals at the greatest risk for acquiring anal STIs are not comfortable disclosing and therefore are not receiving appropriate care.…”
Section: Discussionsupporting
confidence: 71%
“…Methods for the quantitative phase of this study have been described in detail elsewhere [ 28 ]. Respondent-driven sampling (RDS) is a peer-based chain recruitment method often used to reach hidden populations where enumerating a sampling frame is infeasible [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perceived or experienced stigma and discrimination due to sexual orientation and concerns about confidentiality in the healthcare setting are structural barriers to accessing HIV services, particularly in settings where male-to-male sexual practices are criminalized [ 8 , 26 30 ]. The invisibility of MSM in health surveillance programs and limited funding for targeted, affordable, confidential and MSM-sensitive HIV testing and treatment services in Cameroon may also pose policy-level barriers to the delivery of HIV-related services in a setting of high HIV prevalence [ 5 , 27 , 31 – 35 ].…”
Section: Introductionmentioning
confidence: 99%